Shelves of Books, Piles of Books, References and Lists of Books as Performances of Metrics and Expertise - Nguyen, Anna (WritingThreeSixty, 2021)
Since the pandemic, I have participated in or attended many virtual lectures and conferences. Inevitably, I have seen numerous personal libraries, libraries in offices, or walls of books strategically peeking from behind the speaker. Academics, in particular, have spectacular bookshelves. The shelves are overflowing with books, enough to make the bookcases abundant and full, but organized enough so their spines reveal evidence of the title and the author’s name. And the collection of each speaker is a reflection of their research area. An author and professor in a literature department has rows of fiction. Someone who studies food has cookbooks in addition to their stacks of scholars’ monographs published by university presses. A scholar in a field like science and technology studies (STS) will have books with words such as “data”, “the Internet”, “political economy”, and “digital” in their titles.